2005
DOI: 10.1002/jmr.726
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the year 2003 commercial optical biosensor literature

Abstract: In the year 2003 there was a 17% increase in the number of publications citing work performed using optical biosensor technology compared with the previous year. We collated the 962 total papers for 2003, identified the geographical regions where the work was performed, highlighted the instrument types on which it was carried out, and segregated the papers by biological system. In this overview, we spotlight 13 papers that should be on everyone's 'must read' list for 2003 and provide examples of how to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(48 citation statements)
references
References 921 publications
(159 reference statements)
0
48
0
Order By: Relevance
“…References 4, 10, 11, 13, and 18 describe the SPR phenomenon, compare and contrast the different platforms and sensor surfaces that are available, and outline how optical biosensors are implemented in studying a range of interactions. Our surveys of the 2003 and 2004 literature highlight recently published work that demonstrates the wealth of information available from well-designed and properly executed biosensor experiments [15,16].…”
Section: Reviews Methods and Theorymentioning
confidence: 99%
“…References 4, 10, 11, 13, and 18 describe the SPR phenomenon, compare and contrast the different platforms and sensor surfaces that are available, and outline how optical biosensors are implemented in studying a range of interactions. Our surveys of the 2003 and 2004 literature highlight recently published work that demonstrates the wealth of information available from well-designed and properly executed biosensor experiments [15,16].…”
Section: Reviews Methods and Theorymentioning
confidence: 99%
“…All experiments were conducted in 1% methanol, 10% glycerol, 100 mM potassium phosphate (pH 7.4), at flow rate of 100 μl/min, and at 10 °C unless stated otherwise. SPR data were double referenced [31][32][33] and analyzed with Biaevaluation software 4.1 (Biacore AB). Sensorgrams were corrected for organic co-solvent effects [35], but as witnessed by others the use of methanol as the organic co-solvent and the use of suitable control surfaces made correction factors negligible [36].…”
Section: Surface Plasmon Resonancementioning
confidence: 99%
“…All experiments were conducted in 1% methanol, 10% glycerol, 100 mM potassium phosphate (pH 7.4), at flow rate of 100 μl/min, and at 10 °C unless stated otherwise. SPR data were double referenced [31][32][33] During curve fitting and modeling, it was observed that the 'analyte heterogeneity' model contained within the BIAevaluation software consistently fit best to the data, even though experiments were run with chromatographically pure, chirally-resolved, diastereomers of either ITZ or KTZ. This initially surprising result is easily understood upon comparison of the differential equations describing heteroanalyte binding and those describing parallel trajectories for a single analyte.…”
mentioning
confidence: 99%
“…In some cases, non specific adsorption can be reduced by adding CM dextran sodium salt in the samples (Karlsson et al, 1993;Yang et al, 2005). To date, BIAcore and CM5 chip are most widely used equipment and sensor chip (Rich and Myszka, 2005;Rich and Myszka, 2007).…”
Section: Introductionmentioning
confidence: 99%